Impact of sequence type and field strength (1.5, 3, and 7T) on 4D flow MRI hemodynamic aortic parameters in healthy volunteers. Issue 2 (4th August 2020) - Wiesemann, Stephanie; Schmitter, Sebastian; Demir, Aylin; Prothmann, Marcel; Schwenke, Carsten; Chawla, Ashish; von Knobelsdorff‐Brenkenhoff, Florian; Greiser, Andreas; Jin, Ning; Bollache, Emilie; Markl, Michael; Schulz‐Menger, Jeanette
Abstract : Purpose: 4D flow magnetic resonance imaging (4D‐MRI) allows time‐resolved visualization of blood flow patterns, quantification of volumes, velocities, and advanced parameters, such as wall shear stress (WSS). As 4D‐MRI enters the clinical arena, standardization and awareness of confounders are important. Our aim was to evaluate the equivalence of 4D flow‐derived aortic hemodynamics in healthy volunteers using different sequences and field strengths. Methods: 4D‐MRI was acquired in 10 healthy volunteers at 1.5T using three different prototype sequences, at 3T and at 7T (Siemens Healthineers). After evaluation of diagnostic quality in three segments (ascending‐, descending aorta, aortic arch), peak velocity, flow volumes, and WSS were investigated. Equivalence limits for comparison of field strengths/sequences were based on the limits of Bland‐Altman analyses of the intraobserver variability. Results: Non‐diagnostic quality was found in 10/144 segments, 9/10 were obtained at 7T. Apart for the comparison of forward flow between sequence 1 and 3, the differences in measurements between field strengths/sequences exceeded the range of agreement. Significant differences were found between field strengths/sequences for forward flow (1.5T vs. 3T, 3T vs. 7T, sequence 1 vs. 3, 2 vs. 3 [ P < .001]), WSS (1.5T vs. 3T [ P < .05], sequence 1 vs. 2, 1 vs. 3, 2 vs. 3 [ P < .001]), and peak velocity (1.5T vs. 7T, sequence 1 vs. 3 [ P > .001]). All parameters at all field strengths/with all sequences correlated moderately to strongly (r ≥ 0.5). Conclusion: Data from all sequences could be acquired and resulting images showed sufficient quality for further analysis. However, the variability of the measurements of peak velocity, flow volumes, and WSS was higher when comparing field strengths/sequences as the equivalence limits defined by the intraobserver assessments.